FACTORS AFFECTING WORK MOTIVATION OF EMPLOYEES IN BANGKOK LAB AND COSMETIC COMPANY - Mesaengpan, Malee; Sanmuang, Kanokwan; Panniam, Kanchana (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2019)
The objectives of this research were 1) to study motivation for operation of employees in Bangkok Lab and Cosmetic Company, and 2) to compare personal opinions of employees in Bangkok Lab and Cosmetic Company that affect their motivation for operation. The samples were 230 employees in Bangkok Lab and Cosmetic Company using Taro Yamane’s method and selected by simple random sampling. The tool for data collection was the questionnaire verified by 3 experts, with consistency at 0.91. Statistics included frequency, percentage, standard deviation, independent sample T – test, one–way ANOVA, the Scheffe method for pair matching comparison, and Fisher’s Least Significant Difference. Based on the study, it was found 1) the factors affecting work motivation of employees in Bangkok Lab and Cosmetic Company regarding the overview and details, from ascending to descending mean, were relationship with supervisor, management policy, relationship with colleagues, responsibility, job security, job progress, and salary and welfare, respectively. 2) Moreover, employees with different gender, education, and monthly salary in Bangkok Lab and Cosmetic Company Limited did not have an effect towards on work motivation.